Terrestrial ecosystem model performance in simulating productivity and its vulnerability to climate change in the northern permafrost region - Xia, J.; Mcguire, A.D.; Lawrence, D.; Burke, E.; Chen, G.; Chen, X.; Delire, Christine; Koven, C.; Macdougall, A.; Peng, S.; Rinke, A.; Saito, K.; et al. (Journal of Geophysical Research: Biogeosciences, 2017)
[Departement_IRSTEA]Eaux [TR1_IRSTEA]ARCEAU International audience Realistic projection of future climate-carbon (C) cycle feedbacks requires better understanding and an improved representation of the C cycle in permafrost regions in the current generation of Earth system models. Here we evaluated 10 terrestrial ecosystem models for their estimates of net primary productivity (NPP) and responses to historical climate change in permafrost regions in the Northern Hemisphere. In comparison with the satellite estimate from the Moderate Resolution Imaging Spectroradiometer (MODIS; 246 ± 6 g C m